ملامح فلسفة فريديريك نيتشه في رواية الناجون لـ: الزهرة رميج قراءة في فلسفة إرادة القوة و الجمع بين المتناقضات - أقطي, نوال (University of Eloued جامعة الوادي, 2018)
يعرض هذا البحث لملامح فلسفة نيتشه في رواية الناجون لـ: الزهرة رميج لما ثمة من تشابك بين المنجزين الفلسفي والسردي، فقد اتفقت الساردة مع نيتشه في مبدأ إرادة القوة المثبت للذات والمسهم في إدراكها للوجود. وينتظم هذا البحث ضمن أربعة أبعاد جاءت على النحو التالي: 1- الوجود وتماهي الأضداد. 2- المكان ( زحف النقيض نحو نقيضه) 3- الزمن ( سلطة محو التضاد) 4- الذات بين فعلين. This research displays the features of Nietzsche's philosophy in the survivors novel of Zahra Rumij, because there is a tangle between the philosophical and narrative. The narrator agreed with Nietzsche in the principle of the will to power that self-assured and it contributed to self realization of existence. This research is organized into four dimensions as following: 1- The existence and unification of opposites. 2 - place (the march of contrast to its contrast). 3 - time (authority to erase contrast). 4 - the self between two actions
the features of Nietzsche‘s philosophy in the survivors novel of " Zahra Rumij "
مجلة البحوث والدراسات المجلد 15 العدد02 جامعة الوادي
Keywords: الجمع بين المتناقضات؛ إرادة القوة ؛ الصراع؛ فعل المقاومة؛ الذات; Combining contradictions, desire for power, conflict, act of resistance, self.